Why Be Moral? - Himmelmann, Beatrix (De Gruyter, 2015)
What reasons do we have to be moral, and are these reasons more compelling than the reasons we have to pursue non-moral projects? Ever since the Sophists first raised this question, it has been a focal point of debate. Why be Moral? is a collection of new essays on this fundamental philosophical problem, written by an international team of leading scholars in the field.